Factor Inhibitor Testing: An Update from Australasia/Asia-Pacific - Favaloro, Emmanuel J.; Arunachalam, Sandya (Seminars in Thrombosis and Hemostasis, 2025)
Factor VIII (FVIII) inhibitors represent antibodies that develop against coagulation FVIII and reduce FVIII functional activity. FVIII inhibitors may develop in patients with congenital hemophilia A (CHA) in response to infused FVIII (allo-antibodies) or in patients without CHA in a variety of situations (auto-antibodies; acquired hemophilia A). We report updated findings for FVIII inhibitor testing in our geographic region using recent data (testing for the past 5 years; 2020–2024 inclusive) from the RCPAQAP (Royal College of Pathologists of Australasia Quality Assurance Program), an international external quality assessment (EQA) program, with over 80 enrolments for the FVIII inhibitor module. Four samples are assessed each year, with these comprising both FVIII inhibitor negative samples and FVIII inhibitor positive samples with various inhibitor titers. This EQA data largely evidences favorable findings in FVIII inhibitor testing in our jurisdiction, with >99% of test results interpreted correctly by participants for the presence (“detected”) or absence (“not detected”) of FVIII inhibitors in assessed samples. Moreover, most errors in interpretation appear to be transcription or data entry errors rather than analytic errors. The coefficient of variation (CV) values for FVIII inhibitor samples were moderately high, ranging from 25 to 40%, irrespective of the inhibitor titer (range: 3–64 Bethesda units [BU]/mL) or the method (i.e., Bethesda vs. Nijmegen). In conclusion, most laboratories were able to correctly identify the presence versus absence of FVIII inhibitors, although laboratory-reported titers varied moderately.
Keywords: factor VIII inhibitor testing; Bethesda assay; Bethesda unit; Nijmegen Bethesda assay; laboratory testing; external quality assessment; proficiency testing; assay variability